Glacial conditioning and paraglacial sediment reworking in Glen Croe (the Rest and be Thankful), western Scotland. Issue 2 (April 2020) - Finlayson, Andrew
Abstract: Glen Croe, located near the western edge of the Loch Lomond and Trossachs National Park, is a well-known landslide hazard site in Scotland. Debris flows have repeatedly closed the A83 Rest and be Thankful road that passes through the valley, and considerable investment has been directed towards hazard risk reduction. However, little research has focused on the former glaciation and paraglacial response that have played an important role in governing current landscape processes at the site. This paper addresses the knowledge gap by investigating the glacial processes that have shaped and conditioned Glen Croe, and pathways that have characterised subsequent paraglacial sediment transfer. The large-scale valley form results from watershed breaching and interaction between glacier erosion and paraglacial rock slope failures. The distribution of thick glacigenic sediment is conditioned by deposition at former lateral ice margins, which was influenced by topography. Sediment reworking has resulted in accumulation of debris cones and alluvial fans in the upper part of the catchment, and growth of a delta at the outlet. Spatial connectivity mapping supports an interpretation whereby upper Glen Croe is poorly connected to the valley outlet, influencing sediment storage. In contrast, slopes in the lower part of Glen Croe are well connected. Sediment distribution in Glen Croe fits within the context of glaciated valley and paraglacial landsystems, allowing an understanding of sources and transport pathways. In upland infrastructure corridors this type of information is potentially helpful for understanding how landscapes might be affected by renewed sediment reworking under altered threshold conditions.